Implikasi Penggunaan E-money, Literasi Keuangan, dan Sikap Keuangan Terhadap Perilaku Konsumtif - Nurjanah, Rina; Yahya, Adibah; Kosim, Muhammad; Putri, Nabila Khairunnisa; Ningamah, Hurriyatun (Jurnal Ecogen, 2024)
One of the illogical behaviors that affects purchase decisions is consumptive behavior, whitch puts wabts ahead of needs. The use of electronic money, one’s degree of financial ‘s financial literacy, and one’s financial attitudes are some of the variables that influence this behavior. Consumptive behaviour can be decreased by a person’s capacity to manage their usage of electronic money, financial literacy, financial attitude on consumer behavior is the aim of this research. This study analyzes data without making any assumptions using a quantitative descriptive methodology. With 92 individuals in the sample, consistted of students from Pelita Bangsa University college of business and economics. The data sources used are primary and secondary data, whereby the primary data was collected using questionnaires. The results show that e-money and financial literacy have no significant impact on consumptive behaviour, while financial attitudes show a negative influence. The findings contribute to understanding the determinants of consumptive behaviour, especially among students